Leptin, troglitazone, and the expression of sterol regulatory element binding proteins in liver and pancreatic islets - Kakuma, Tetsuya (National Academy of Sciences, 2000)
Overaccumulation of lipids in nonadipose tissues of obese rodents may lead to lipotoxic complications such as diabetes. To assess the pathogenic role of the lipogenic transcription factor, sterol regulatory element binding protein 1 (SREBP-1), we measured its mRNA in liver and islets of obese, leptin-unresponsive fa/fa Zucker diabetic fatty rats. Hepatic SREBP-1 mRNA was 2.4 times higher than in lean +/+ controls, primarily because of increased SREBP-1c expression. mRNA of lipogenic enzymes ranged from 2.4- to 4.6-fold higher than lean controls, and triacylglycerol (TG) content was 5.4 times higher. In pancreatic islets of fa/fa rats, SREBP-1c was 3.4 times higher than in lean +/+ Zucker diabetic fatty rats. The increase of SREBP-1 in liver and islets of untreated fa/fa rats was blocked by 6 weeks of troglitazone therapy, and the diabetic phenotype was prevented. Up-regulation of SREBP-1 also occurred in livers of Sprague–Dawley rats with diet-induced obesity. Hyperleptinemia, induced in lean +/+ rats by adenovirus gene transfer, lowered hepatic SREBP-1c by 74% and the lipogenic enzymes from 35 to 59%. In conclusion, overnutrition increases and adenovirus-induced hyperleptinemia decreases SREBP-1c expression in liver and islets. SREBP-1 overexpression, which is prevented by troglitazone, may play a role in the ectopic lipogenesis and lipotoxicity complicating obesity in Zucker diabetic fatty rats.